Adding value to the decision-making process of mega projects: Fostering strategic ambiguity, redundancy, and resilience. (November 2015) - Giezen, Mendel; Salet, Willem; Bertolini, Luca
Abstract: Current practice in decision-making about mega projects seems to be aimed at reducing complexity by simplification. However, this is often detrimental to the resilience and added value of these projects. This article uses the concept of strategic capacity for analyzing the decision-making process on mega projects. This concept consists of three elements: strategic ambiguity (the tension between different purposes and goals), redundancy (having more options than necessary from an efficiency perspective) and resilience (is the process reactively or proactively resilient to outside demands?). Two transport mega projects in the Netherlands are analyzed. Our analysis demonstrates that creative solutions and added value are to be found in the recombination of policy options made possible by enhancing strategic capacity. Highlights: Redundancy in actors and knowledge is necessary to overcome dead-lock. Strategic ambiguity prevents lock-in in decision-making and planning mega projects. Reactive resilience leads to lesser quality projects than pro-active resilience.